1994
DOI: 10.1136/gut.35.11.1599
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria in inflammatory bowel disease.

Abstract: Microalbuminuria independently predicts the development of nephropathy and increased cardiovascular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
64
2
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 37 publications
5
64
2
1
Order By: Relevance
“…Th ere is no clear relationship between dose and the risk of nephrotoxicity, raising the possibility that this reaction might be idiosyncratic ( 100 ). In addition, patients with active IBD may develop an increase in microalbuminuria in the presence of active disease ( 101 ). Furthermore in an epidemiologic study of over 20,000 IBD patients from the UK, there was not an increased incidence of nephrotoxicity in IBD patients taking mesalamine compounds, compared with IBD patients without mesalamine use ( 102 ).…”
Section: Recommendations For Management Of Mild -Moderate Distal Colitismentioning
confidence: 99%
“…Th ere is no clear relationship between dose and the risk of nephrotoxicity, raising the possibility that this reaction might be idiosyncratic ( 100 ). In addition, patients with active IBD may develop an increase in microalbuminuria in the presence of active disease ( 101 ). Furthermore in an epidemiologic study of over 20,000 IBD patients from the UK, there was not an increased incidence of nephrotoxicity in IBD patients taking mesalamine compounds, compared with IBD patients without mesalamine use ( 102 ).…”
Section: Recommendations For Management Of Mild -Moderate Distal Colitismentioning
confidence: 99%
“…It is therefore not surprising that several studies have shown microalbumin excretion to be positively correlated with blood pressure, especially at pressures Ͼ150/90 mm Hg. 2,9 Thus microalbumin excretion reflects minute by minute changes in vascular endothelial permeability and has been found to be associated with many inflammatory processes such as bacterial meningitis, 10 rheumatoid arthritis, 11 inflammatory bowel disease, 12 acute pancreatitis, 13 trauma 14 and surgery. 15 In each condition microalbumin excretion is proportional to the severity of the condition, and since it occurs within minutes of acute insults, is of value in predicting later complications associated with interstitial oedema, such as acute respiratory distress syndrome.…”
Section: In This Issue Drs Reid Et Almentioning
confidence: 99%
“…If MAL represented vascular numbers of enrolled patients have further addressed damage and had prognostic implications, hypertenthe controversy on the role of MAL as a cardiovascusive target organ damage may thus be more common lar risk factor in hypertension. 20 24 suggesting increased microvascular permeability probably secondary to group was 31%, 24%, 6% and 7% which was significantly higher compared to corresponding values inflammatory mediators such as the cytokines. 24 However, MAL may also be considered to reflect in the normoalbuminuric group (22%, 14%, 4% and 5%, respectively; P Ͻ 0.0001).…”
mentioning
confidence: 81%
“…20 24 suggesting increased microvascular permeability probably secondary to group was 31%, 24%, 6% and 7% which was significantly higher compared to corresponding values inflammatory mediators such as the cytokines. 24 However, MAL may also be considered to reflect in the normoalbuminuric group (22%, 14%, 4% and 5%, respectively; P Ͻ 0.0001). local renal dysfunction characterised by increased intraglomerular pressure and filtration fraction, In this issue of the Journal of Human Hypertension, we report a study by Jensen et al 21 of 1254 leading to increased transglomerular membrane albumin passage and subsequently nephrosclerosis.…”
mentioning
confidence: 81%
See 1 more Smart Citation